Study of the utilization of main crop straw resources in Southern China and its potential as a replacement for chemical fertilizers - Mu, Guiting; Xu, Lifu; Zhang, Jiachun (Frontiers in Plant Science, 2024)
In this study, based on the statistical yearbook and relevant literature data. Study on the total amounts of the resources and chemical fertilizer replaceability of straw of seven crops in Southern China in 2021. The study found that the total amount of straws in South China in 2021 is 270 million tons, which the middle and lower reaches of the Changjiang is the most. The amount of straw nutrients nitrogen (N), P2O5 and K2O returned to the field is 1.54×1010 t, 8.54×105 t, 4.70×109 t, respectively. The total amount of returned farmland accounting for 82.20 % of the total amount of straw nutrient resources. In the corn rice monoculture area, two-thirds of the rice straw returned to the field can completely replace the amount of potassium fertilizer used by rice in the next season; In the rice wheat rotation area, two-thirds of the rice straw returned to the field can completely replace the amount of potassium fertilizer used by wheat. After the wheat straw returned to the field, the amount of chemical nutrients used to replace rice is 17.20 % (N), 19.20 % (P2O5) and 61.80 % (K2O). Is an important way to reduce fertilizer application and increase efficiency.